FAKTOR ANAK PUTUS SEKOLAH TINGKAT SMP DI DESA BUMI REJO KECAMATAN BARADATU - Noor Rizqa; I Gede Sugiyanta; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2016)
The objective of this research was to analyze factors which causing children dropouts at the level of junior high school in Bumi Rejo village, Baradatu districts. The method used in research was descriptive method and the subjects of this research were the parents of dropout students. Data collection technique used observation techniques, interview techniques and questionnaire techniques. The results showed that the 22 parents of children who are droped out of school are 86,4 % are low income, 86,4% have many children, 77,3% have less educated and all these droputs students have to reach distance of more than 5 kilometers to school. So, it can be concluded that the factors that these factors caused the children dropouts of school in Bumi Rejo village.Penelitian ini bertujuan untuk mengetahui faktor putus sekolah tingkat SMP yang ada di Desa Bumi Rejo Kecamatan Baradatu. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif, subjek penelitiannya adalah orang tua anak putus sekolah. Teknik pengumpulan data menggunakan teknik observasi, tekhnik wawancara, dan teknik kuisioner. Dari 22 orang tua anak putus sekolah 86,4 % orang tua berpenghasilan rendah, 86, 4 % memiliki anak banyak, 77,3% orang berpendidikan rendah dan seluruh anak putus sekolah ini berjarak diatas 5 km untuk mencapai sekolah, sehingga disimpulkan bahwa faktor-faktor inilah yang menyebabkan anak-anak di Desa Bumi Rejo putus sekolah.Kata kunci: faktor, orang tua, anak putus sekolah.